EFEKTIVITAS JUS BUAH BIT DAN TABLET BESI (FE) TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL ANEMIA RINGAN - Phounna, Rahmatun; Isnani, Darana; Fazira, Frisca; Fazlaini, Risna (Jurnal Medikes (Media Informasi Kesehatan), 2024)
The risk of maternal mortality in developing countries is estimated to be one in 29 deliveries, while in developed countries it is one in 29,000 deliveries. The average mortality caused by anemia in Indonesia and Asia is estimated to be 7.26%. One of the health problems that contributes to the maternal mortality rate is anemia. The target of pregnant women with anemia at the Darul Imarah Community Health Center in December 2023 is around 686 individuals. This study aims to analyze the effectiveness of beetroot juice and iron tablets (Fe) in pregnant women with mild anemia. The study uses a quasi-experimental method. The experimental group was divided using a nonequivalent control group design into a treatment group (beetroot juice) and a control group (iron tablets). The research sample consists of pregnant women with anemia and hemoglobin levels of ≥ 9-10 gr%, totaling 30 samples. The study, conducted over 10 days, found that the average pretest and posttest hemoglobin levels in the experimental group were 10.38 (SD 0.79) and 13.64 (SD 0.50), respectively. The average pretest and posttest hemoglobin levels in the control group were 10.38 (SD 0.74) and 13.69 (SD 0.49), respectively. Paired t-test analysis showed a significant difference in hemoglobin levels before and after treatment in each group (p<0.05). Based on this research, it is recommended that the government and healthcare workers enhance education and socialization regarding the benefits of beetroot juice and iron tablets for pregnant women with mild anemia as an alternative natural supplement.